Steroid Receptor Coactivator-Interacting Protein (SIP) Alleviates Ischemic Cerebral Infarction Damage Through the NF-κB Pathway - Yu, Min; Li, Yan; Tan, Xianpei; Hu, Qiao (Hormone and Metabolic Research, 2022)
Ischemic stroke leads to high mortality and disability rates in humans. Cerebral ischemic injury has a severe complex pathophysiological mechanism. The abnormal release of inflammatory cytokines will cause brain tissue damage and destroy the blood-brain barrier integrity, which aggravates the process of brain injury. Therefore, attenuating the level of inflammatory response is critical for the therapy of cerebral ischemia injury. This study examined the rule of SIP treatment to support neuron protective effect after cerebral injury in an animal model of middle cerebral artery occlusion (MCAO). After ischemia/reperfusion, neurological function, neuroglia cells activation, infarction volume, brain water content, brain tissue apoptosis ratio, and inflammatory response were assessed, and quantitative PCR and western blot were also detected, respectively. Treatment of SIP ameliorated neurological dysfunction, brain infarction, brain edema, and brain cell apoptosis after MCAO operation. Overexpression SIP also suppressed pro-inflammatory cytokines release. Furthermore, the protective effect of SIP on brain injury occurs through reduced neuroglia cells activation through downregulation of the NF-κB pathway. In summary, the present work indicated that SIP prevents ischemic cerebral infarction-induced inflammation and apoptosis by blocking inflammasome activation via NF-κB signaling pathway. Those results suggest that SIP treatment is an attractive strategy for prevention of ischemic cerebral infarction.
Keywords: ischemic cerebral infarction; steroid receptor coactivator-interacting protein; middle cerebral artery occlusion; inflammation; NF-κB